An investigation into added resistance of vessels advancing in waves. (1st September 2016) - Hong, Liang; Zhu, Ren-chuan; Miao, Guo-ping; Fan, Ju; Li, Shuai
Abstract: The hydrodynamic forces and motions of ship advancing in waves are estimated by using 3D frequency domain potential flow theories. The 3D translating and pulsating (3DTP) source panel method is employed to solve the radiation and diffraction potential problems, in which a semi-analytical scheme is established to get more robust results of integration of Green's function over panels. Added wave resistance is mainly categorized into the contributions of radiation and diffraction. The added wave resistance due to radiation motion of ship is evaluated by the radiation energy principle according to 3D hydrodynamic coefficients and ship motions, while the one due to diffraction is calculated based on steady-state force formula. The motions and added wave resistances of Wigley III hull and S175 containership advancing in waves with various forward speed are calculated and analyzed in frequency domain based on the above mentioned methods. The numerical results are validated for the models by comparing them with experimental data. The results by classic methods commonly used in engineering and the data from published papers are plotted together for comparison and discussion. Better agreement with experimental data in the prediction of peak value and its frequency of added resistance is achieved by present method. It also indicates that the correction of relative motion amplitude should be taken into account so as to improve the accuracy. Component analyses of added wave resistance are carried out and the results show the percentages of radiation part and diffraction part at various frequency respectively. The present method is of satisfactory accuracy and efficiency, which provides a rapid and robust approach to predict added wave resistance of ships voyaging in waves. Highlights: A semi analytical scheme is established to get more robust results of panel integration. Added resistance is categorized into the contributions of radiation and diffraction. 3D radiation energy method is used to evaluate radiation added resistance. Results by different methods are compared and discussed.